Managing phosphorus : under acid soils environment - Musa, Mohamed Hanafi (Universiti Putra Malaysia Press, 2010)
Malaysia lies within the world’s humid tropical region with high humidity, abundant annual rainfall (2,000-3,000 mm), and very little variation in temperature (averaging 27°C). As a result, the soils are highly weathered with low pH, high in aluminium (Al), and of poor nutrient status. These soils are inherently low in water-, diluted acid- or alkali-soluble phosphorus (P) with values of less than 10 mg P kg-1 (Owen, 1947; 1953), while total soil P for soils suitable for agriculture practices is commonly less than 300 mg P kg-1 soil (Law and Tan, 1973). Consequently, P deficiency is widespread and P fertilisers are required to improve the fertility status of the soil for crop production. Phosphorus is one of the major elements for plant nutrition and is usually taken up by plants in relatively smaller amounts compared to nitrogen (N) or potassium (K). Phasphorus occurs in plants in numerous forms, such as phosphorylated sugars and alcohols, and as phospholipids which have a wide range of functions (Tisdale and Nelson, 1975). The main function is in energy transfer as a component of adenosine triphosphate (ATP). On hydrolysis, the high energy pyrophosphate bond in ATP releases energy to drive other plant processes, such as those involved in the active uptake of plant nutrients. Although the nutrient status of Malaysian soils is poor, especially for P, a substantial amount of Malaysia’s income (RM 55.0 billion) is expected to be derived from agricultural activities in 2010 (Wong, 2007). The major export contributors (54.5% of total agricultural exports) are oil palm, rubber, cocoa, tea, and pepper crops which are planted in the estate and sub-estate sectors. The success of such plantation-based crops in Malaysia depends on chemical fertiliser inputs, such as that of N, P, and K.